CLASSIFICATION OF STUDENT ERRORS IN SOLVING THE QUADRATIC EQUATION AND QUADRATIC FUNCTION IN CLASS IX SMP JUARA PEKANBARU - Adi Hamdani; Nurul Sadrina (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2020)
The aims of this researches to classification the mistakes made by students osf SMP Juara Pekanbaru in solving the equation of square and the function of square. This research was conducted in SMP Juara pekanbaru in the odd semester of Academic Year 2019/2020. This research uses a descriptive method with research form is a case study. The subject of his research is the IX Class (ninth grade). The result of this study indicate that systematic errors are as many as 6 errors or equal to 5,50%, random errors that is as much as 11 errors or equal to 10,09%, mistake carelessness as much as 111 mistakes or by 84,41%.